PSYCHODIAGNOSTICS OF DISTINGUISHING TWINS FROM EACH OTHER - Izatovna, Toyirova Shakhlo (International Journal of Psychosocial Rehabilitation, 2020)
In this article, a theoretical and practical analysis of the results of the study on the manifestation of individual psychological characteristics and the reasons for characterizing personality factors in twins was revealed, using psychodiagnostic methods, in determining different aspects of twins.